Paraneoplastic bullous pemphigoid masquerading as hand-foot syndrome: a case report of rare entity - Mohan, Subhatharshni; Abdul Rahim, Nazatul Shima; Salleh, Amizatul Aini; Mahayidin, Hasni; Bakrin, Ikmal Hisyam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Bullous pemphigoid (BP) is a chronic and the most frequent immune-mediated subepidermal blistering disorder which mainly affects elderly individuals. The autoantibodies produced following T-cell dysregulation are directed against BP180 (BPAg2) and BP230 (BPAg1), hemidesmosomal proteins located in the basement membrane zone (BMZ) of the epidermis. BP may present with polymorphic dermatological features including non-bullous manifestations and blisters. Therefore, a wide range of differential diagnoses such as eczema, urticaria, pemphigus and the differentials for subepidermal blister with eosinophils such as epidermolysis bullosa acquisita (EBA) and bullous drug eruptions should be considered in such cases. The associations of solid organ internal malignancies and BP are quite rare and vary between studies. Here, we present a case of paraneoplastic bullous pemphigoid (PNBP) in a patient with underlying renal cell carcinoma who was initially diagnosed with worsening hand-foot syndrome (HFS) which has led to withdrawal of his oral chemotherapy treatment.